2010
DOI: 10.2131/jts.35.941
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of the gene for homeobox protein HOXB13 by siRNA confers resistance to methylmercury on HEK293 cells

Abstract: -Methylmercury is an environmental pollutant that causes severe central nervous system disorders. We searched for transcription factors involved in the development of methylmercury toxicity and found that the decreased expression of a homeobox protein, HOXB13, in HEK293 cells conferred strong resistance to methylmercury. Key words: Methylmercury, Homeobox protein, HOXB13, Transcription factorCorrespondence: Akira Naganuma (E-mail: naganuma@mail.pharm.tohoku.ac.jp) Toxicogenomics/proteomics ReportThe Journal of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…Sequences of siRNAs, used in this study, are listed in Figure S1. Knockdown efficiency of HOXB13 siRNA was confirmed in previous report [5,6]. Specificity of all siRNAs was predicted by manufactures.…”
Section: Cell Culture and Transfectionsupporting
confidence: 77%
See 1 more Smart Citation
“…Sequences of siRNAs, used in this study, are listed in Figure S1. Knockdown efficiency of HOXB13 siRNA was confirmed in previous report [5,6]. Specificity of all siRNAs was predicted by manufactures.…”
Section: Cell Culture and Transfectionsupporting
confidence: 77%
“…Previously, we identified the homeobox protein B13 (HOXB13), a transcription factor, as an intracellular factor involved in the enhancement of methylmercury toxicity [5] and established its relationship to cytotoxicity caused by an oxidative stress inducer and a thiol group modifier [6]. HOXB13 is highly expressed in the developmental stages of mice, especially in the chorda and posterior mesoderm, and has been suggested to be involved in the formation of normal nerve tubes by the induction of apoptosis [7].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the research group led by Dr. Naganuma has found a large number of proteins that are resistant or hypersensitive to MeHg (Hwang et al, 2007(Hwang et al, , 2010a(Hwang et al, , 2010b(Hwang et al, , 2010c(Hwang et al, , 2011b(Hwang et al, , 2012a(Hwang et al, , 2012b(Hwang et al, , 2013b. For example, they found that L-glutamine:D-fructose-6-phosphate amidotransferase (GFAT), which is an essential enzyme for catalyzing the synthesis of glucosamine-6-phosphate from glutamine and fructose-6-phosphate, is a factor that confers MeHg-resistance and that GFAT is the intracellular target molecule for MeHg toxicity Naganuma et al, 2000).…”
Section: Attempts To Identify Cases Of the S-mercuration Of Proteinsmentioning
confidence: 99%
“…First-strand cDNA synthesis was carried out using the PrimeScript TM RT reagent kit (Takara, Shiga, Japan). Quantitative real-time PCR was performed using SYBR Premix EX Taq (Takara) and a Thermal Cycler Dice ® (Takara) (Hwang et al, 2010a;Tokumoto et al, 2011). PCR primers used were: CCL2, 5'-TTGTCACCAAGCTCAAGAGAGA-3' (sense) and 5'-GAGGTGGTTGTGGAAAAGGTAG-3' (antisense); CCL4, 5'-CAAACCTAACCCCGAGCAACAC-3' (sense) and 5'-GGTCTCATAGTAATCCATCACAAAGC-3' (antisense); CCL7, 5'-AATGCATCCACATGCTGCTA-3' (sense) and 5'-CTTTGGAGTTGGGGTTTTCA-3' (antisense); CCL9 5'-TGTTTCACATGGGCTTTCAA-3' (sense) and 5'-TTGTAGGTCCGTGGTTGTGA-3' (antisense); CCL12, 5'-GTCCTCAGGTATTGGCTGGA-3' (sense) and 5'-GGGTCAGCACAGATCTCCTT-3', (antisense); and GAPDH, 5'-ATCACCATCTTCCAGGAGCGA-3' (sense) and 5'-AGGGGCCATCCACAGTCTT-3' (antisense).…”
Section: Measurement Of Chemokine Expression Using Quantitative Real-mentioning
confidence: 99%